Recent Advances in Molten-Carbonate Membranes for Carbon Dioxide Separation: Focus on Material Selection, Geometry, and Surface Modification. (29th October 2021) - Afzal, Shabana; Khan, Atif
Abstract : Membranes for carbon dioxide permeation have been recognized as potential candidates for CO2 separation technology, particularly in the energy sector. Supported molten-salt membranes provide ionic routes to facilitate carbon dioxide transport across the membrane, permit the use of membrane at higher temperature, and offer selectivity based on ionic affinity of targeted compound. In this review, molten-carbonate ceramic membranes have been evaluated for CO2 separation. Various research studies regarding mechanisms of permeation, properties of molten salt, significance of material selection, geometry of support materials, and surface modifications have been assessed with reference to membrane stabilities and operational flux rates. In addition, the outcomes of permeation experiments, stability tests, selection of the compatible materials, and the role of interfacial reactions for membrane degradation have also been discussed. At the end, major challenges and possible solutions are highlighted along with future recommendations for fabricating efficient carbon dioxide separation membranes.